x+6(x-1)=7(3-x)

Simple and best practice solution for x+6(x-1)=7(3-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+6(x-1)=7(3-x) equation:


x+6(x-1)=7(3-x)

We simplify the equation to the form, which is simple to understand
x+6(x-1)=7(3-x)

Reorder the terms in parentheses
x+(+6x-6)=7*(3-x)

Remove unnecessary parentheses
+x+6x-6=+7+*(+3-x+)

Reorder the terms in parentheses
x+6x-6=+(+21-7x)

Remove unnecessary parentheses
+x+6x-6=+21-7x

We move all terms containing x to the left and all other terms to the right.
+1x+6x+7x=+21+6

We simplify left and right side of the equation.
+14x=+27

We divide both sides of the equation by 14 to get x.
x=1.92857142857

See similar equations:

| -7x-105=39-15x | | r=110a-20 | | 2x*0.5x*45=x | | 3*4x=18x | | 2y-11=7 | | 12-(3x+10)=7(5-2x) | | 199t-5/9-3=7.5 | | -136+4x=44-6x | | -10x-42=-12x+16 | | l-5.5l= | | y+4=3y+8 | | 14-3=x-2 | | 0.3x+0.6=0.25(x+3) | | 5-9x=-50 | | 11x-22=14+10x | | 5/6x=6-11/12x | | -42-5x=-7x+26 | | F=5/2(n-85) | | -81-4x=73-11x | | x^3y+2y=1 | | -5*-2*-6= | | 5r^2+27r+28=0 | | -5*-10*-6= | | 10*-6= | | 2x-138=94+10x | | 2+2(-8y+7)=3(6y-8)+4 | | f(h)=380+0.75(380)+0.50(380)+3.5h | | 3x+40=60+2x | | 2x+40=60+2x | | -7m+10=-39 | | -1/3w+5/6=-2/5w+1/6 | | 8+2x=-4 |

Equations solver categories